Exploring the Therapeutic Role of Physical Activity in Psychotic Disorders: Cognitive, Somatic, and Mental Health Impacts - Fikas, Klaudia; Chwaliszewski, Kamil; Waz, Dorota; Mazur, Michał; Szarłowicz, Jakub; Goliszek, Zofia; Sobek, Karolina Łucja; Tabin-Barczak, Wiktoria; Sokołowska , Aldona; Samuła, Sebastian (Quality in Sport, 2025)
Introduction and Purpose: Psychotic disorders, such as schizophrenia, significantly affect both physical and mental health, often leading to a reduced quality of life. These conditions are commonly associated with somatic symptoms, fatigue, and impaired psychosocial functioning. This review aims to explore the impact of physical activity on psychotic disorders, focusing on its effects on somatic symptoms, fatigue, and overall well-being, while examining the underlying mechanisms and its potential as an adjunctive therapy. Material and Methods: This systematic review was based on a comprehensive search of peer-reviewed literature in PubMed, covering studies published between 2020 and 2024. Studies eligible for inclusion were observational research, clinical trials, and meta-analyses that examined the role of physical activity in alleviating somatic symptoms, reducing fatigue, and improving overall well-being in individuals with psychotic disorders. Results: The literature review indicates that physical activity has the potential to improve somatic symptoms, reduce fatigue, and enhance overall well-being in individuals with psychotic disorders. Exercise interventions, particularly aerobic and resistance training, seem to benefit both positive and negative symptoms of psychosis, with notable improvements in cognitive function. Further research is necessary to determine the optimal exercise parameters. Conclusions: This review underscores the significant therapeutic potential of physical activity in alleviating somatic symptoms and improving the overall quality of life in individuals with psychotic disorders. Studies should investigate the neurobiological mechanisms behind the beneficial effects of physical activity in psychosis, such as stress responses and neuroplasticity. Integrating physical activity into standard treatment regimens could significantly improve patient outcomes in this population.